Prognostic impact of coronary chronic total occlusion on recurrences of ventricular tachyarrhythmias and ICD therapies - Behnes, Michael; Mashayekhi, Kambis; Kuche, Philipp; Kim, Seung‑Hyun; Schupp, Tobias; Zworowsky, Max von; Reiser, Linda; Kern-Bollow, Armin; Taton, Gabriel; Reichelt, Thomas; Borggrefe, Martin; Ellguth, Dominik; et al. (Clinical research in cardiology, 2021)
Despite a few studies evaluating the prognostic impact of coronary chronic total occlusion (CTO) in implantable cardioverter defibrillator (ICD) recipients, the impact of CTO on different types of recurrences of ventricular tachyarrhythmias, as well as their predictors has not yet been investigated in CTO patients.